Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XV): Two new synonyms of D. kansuense - Li, Hui-Min; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2018)
We demonstrate that both Delphinium iliense var. macrocentrum and D. kansuense var. villosiusculum are morphologically identical with D. kansuense (Ranunculaceae). We therefore reduce them to the synonymy of D. kansuense herein. Lectotypification is proposed for D. crassifolium var. tanguticum, another synonym of D. kansuense.